Health status of UK care home residents: a cohort study - Gordon, Adam L.; Franklin, Matthew; Bradshaw, Lucy; Logan, Pip; Elliott, Rachel; Gladman, John R.F. (Oxford University Press, 2014)
Background: UK care home residents are often poorly served by existing healthcare arrangements. Published descriptions of residents’ health status have been limited by lack of detail and use of data derived from surveys drawn from social, rather than health, care records.